PENGARUH BIAYA TRANSAKSI TERHADAP PERIODE KEPEMILIKAN SAHAM DI BURSA EFEK INDONESIA - Silalahi, Donalson (UNIKA Santo Thomas, 2012)
The theoretical suggests that, the higher transaction cost resulting in longer holding periods. Based on this concept, many studies have been done and show that: the transaction cost has a positive and significant effect on holding period. Other research suggests that: the transaction cost has a negative and significant effect on holding period. Therefore, the issue of this research is to explain why the influence of the transaction cost on holding period are not consistent. To achieve these objectives, to conducted research in Indonesia Stock Exchange during the years 2010 - 2011 and using the purposive sampling as the sampling technique. Samples were observed at 1.056 and data were analyzed using the multiple regression. The results showed that: (1), the effect of transaction cost on holding period depends on the components of transaction cost (information friction and real friction). (2), information friction has a negative and significant effect on holding period. (3), real friction has a positive and significant effect on holding period. (4), the influence of information friction and real friction on holding period increase the higher of traded volume and listed shares. (5), the relationship of decomposition of transaction cost on holding period is monotonic. Based on the results of this research: (1), in making decisions regarding the holding period of shares in Indonesia Stock Exchange, investors should consider the component of transaction cost (information friction and real friction). In addition to the information, in determining the holding period, investors should also attention the trading volume and the number of shares listed. (2), transaction cost and its components can be used in shaping investors' portfolios and investment horizon period. (3), transaction cost can be used the company in issuing shares.